Marketing analytics using excel: A beginner`s guide - Kaurav, Rahul Pratap Singh; Thomas, Asha (New Delhi Sage, 2025)
This introductory guide to marketing analytics using Microsoft Excel provides a broad and easy-to-understand overview of marketing analytics for those who are new to the subject.